2006
DOI: 10.1074/jbc.m610023200
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Represses Signaling through the Mammalian Target of Rapamycin in Muscle Cells by Enhancing Expression of REDD1

Abstract: The mammalian target of rapamycin (mTOR), a critical modulator of cell growth, acts to integrate signals from hormones, nutrients, and growth-promoting stimuli to downstream effector mechanisms involved in the regulation of protein synthesis. Dexamethasone, a synthetic glucocorticoid that represses protein synthesis, acts to inhibit mTOR signaling as assessed by reduced phosphorylation of the downstream targets S6K1 and 4E-BP1. Dexamethasone has also been shown in one study to up-regulate the expression of RED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
218
4
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 45 publications
11
218
4
4
Order By: Relevance
“…Cros et al (19) identified REDD2 (also named SMHS1) as a highly upregulated gene in soleus muscle undergoing atrophy following 14 days of hindlimb unloading (78). Biochemical studies of both REDD1 and REDD2 found that they inhibit mTOR kinase activity in non-muscle and muscle cells downstream of Akt/PKB but upstream of TSC2 (14,18,89,105). In skeletal muscle, REDD1 has been shown to inhibit mTOR signaling and protein synthesis in response to dexamethasone and alcohol intoxication (67,105).…”
Section: Stress Response Genes Redd1/redd2 and Mtor Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cros et al (19) identified REDD2 (also named SMHS1) as a highly upregulated gene in soleus muscle undergoing atrophy following 14 days of hindlimb unloading (78). Biochemical studies of both REDD1 and REDD2 found that they inhibit mTOR kinase activity in non-muscle and muscle cells downstream of Akt/PKB but upstream of TSC2 (14,18,89,105). In skeletal muscle, REDD1 has been shown to inhibit mTOR signaling and protein synthesis in response to dexamethasone and alcohol intoxication (67,105).…”
Section: Stress Response Genes Redd1/redd2 and Mtor Signalingmentioning
confidence: 99%
“…Biochemical studies of both REDD1 and REDD2 found that they inhibit mTOR kinase activity in non-muscle and muscle cells downstream of Akt/PKB but upstream of TSC2 (14,18,89,105). In skeletal muscle, REDD1 has been shown to inhibit mTOR signaling and protein synthesis in response to dexamethasone and alcohol intoxication (67,105). In addition, Kimball et al (65) found that rapid degradation of REDD1 in muscle was associated with enhanced mTOR signaling.…”
Section: Stress Response Genes Redd1/redd2 and Mtor Signalingmentioning
confidence: 99%
“…Several stressors such as energy depletion [6], ER stress [7,8], hypoxia [9,10], DNA damage by irradiation [11] and chemicals [12] induce the expression of REDD1. Additionally REDD1 expression is increased by pharmacological derivatives of cortisol such as dexamethasone [8,13] and by insulin [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, REDD1 and REDD2 have been identified as negative regulators of mTOR (17). REDD1 is altered in response to various cellular stresses such as hypoxia, dexamethasone, starvation, and muscle contraction (11,17,24,48,55). REDD1 has been shown to interact with 14 -3-3 and modify the function of the tuberous sclerosis 1 (TSC1) and 2 (TSC2) complex (18) leading to inhibition of mTOR signaling.…”
mentioning
confidence: 99%